The Impact of Title IX on Career Opportunities in Intercollegiate Athletic Administration - Bower, Glenna G.; Hums, Mary A. (Journal of Intercollegiate Sport, 2013)
The purpose of this study was to examine the impact of Title IX on the careers of men and women working in intercollegiate athletic administration. The participants (N = 1275) for this study were women (n = 497) and men (n = 778) working in intercollegiate athletic administration at NCAA Divisions I, II, II, as well as at NAIA schools and junior colleges. The participants completed the Female Sport Manager Career Survey and provided demographic and qualitative data. The primary impacts on careers described by the women in the study were (a) increased job opportunities for women, (b) no impact, and (c) increased opportunities for participation. The men, on the other hand, indicated the greatest impacts on careers as (a) no impact, (b) discrimination against qualified men, and (c) increased job opportunities for women. More research is needed to further examine these perceived impacts and how they affect the culture of an intercollegiate athletic department.